SERVICE QUALITY AT RSUD DR. PIRNGADI MEDAN IN THE CONTEXT OF THE IMPLEMENTATION OF MEDAN CITY REGULATION NUMBER 4 OF 2012 ON THE CITY HEALTH SYSTEM - Royandi Simorangkir; Victor Lumbanraja (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
This study examines the quality of health services at RSUD Dr. Pirngadi Medan within the framework of the implementation of Medan City Regulation Number 4 of 2012 concerning the City Health System. Using the SERVQUAL model tangibles, reliability, responsiveness, assurance, and empathy this research adopts a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving hospital management, health personnel, and patients. The findings indicate that service quality has not yet reached an optimal level. Constraints in physical facilities, long waiting times, limited responsiveness, and suboptimal communication remain key issues. Although the regulation has been implemented formally, its effectiveness is hindered by managerial limitations, human resource constraints, and inadequate infrastructure. Strengthening hospital management, improving staff competencies, and enhancing supervision are necessary to improve service quality and policy implementation outcomes